Deformation and Fracture of β‐Silicon Nitride Micropillars. Issue 2 (22nd December 2014) - Csanádi, Tamás; Chinh, Nguyen Q.; Szommer, Péter; Dusza, Ján; Lenčés, Zoltán; Šajgalík, Pavol; Reimanis, I.
<x xml:space="preserve">Abstract</x> Room‐temperature deformation and fracture behaviors under microcompression of single crystal β‐silicon nitride (Si3N4) micropillars were investigated. Pillars were fabricated by focused ion beam (FIB) in large Si3N4 grains, located close to the basal and prismatic orientations, selected by electron backscatter diffraction (EBSD). The micromechanical test and the damage characterization were performed by nanoindentation and scanning electron microscopy (SEM), respectively. The elastic, plastic, and fracture properties, such as Young's modulus, yield stress, and rupture stress are considerably influenced by the pillar orientation. The activation of the <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3jj8nq82" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />{101¯0}[0001]</alternatives> type slip system was identified in case of basal oriented micropillars.